(untitled) (Research, Society and Development, 2020)
Prominent on the northeastern semiarid of Brazil as a plant of exceptional foraging capacity and notorious resistance to the local adversities, the forage watermelon (Citrulus lanatus cv. Citroides) is yet another species whose little knowledge limits it as a commercial alternative. The research was conducted on the experimental area of the Federal University of Piauí, in Teresina, from June to August 2019, aiming to identify the reactions of plants in an open and protected environment, conducted in expanded polystyrene trays. The experimental design consisted of randomized blocks with 4 replications and treatments in a 2x2 factorial arrangement, with the type of tray (72 and 128 cells) and environment (open sky and protected cultivation) factors. The trays were filled with commercial substrate and chemical fertilizer, distributed on an open sky supports and inside a protected cultivation unit with 50% shading. To measure the responses, the parameters were evaluated: height of the seedling from the cleavage to the terminal bud of the stalk, length of the root, weight of the fresh matter of the aerial part and of the cotyledon leaves, being possible to conclude that: the seedlings react more to the type of tray than to the cultivation environment, where larger trays (72 cells) positively influence the weight of cotyledon leaves, the number of leaves and the weight of fresh matter in the aerial part. Both the environment and the type of tray interfere with the length of the root, getting deeper in the 72 cell units and open environment. Regardless of the type of tray, the plant is going to be greater in an open environment.